Self-Reliance and Responsibility Education in Islamic Junior High Schools: A Humanistic Psychology Approach - Kunaepi, Aang; Syukur, Fatah; Ikhrom, Ikhrom (Madania: Jurnal Kajian Keislaman, 2024)
This study aims to analyze strategies for strengthening independent character and responsibility in Islamic-based secondary schools, focusing on the implementation of humanistic concepts in learning. The research method used was qualitative, with data collection through observation, in-depth interviews, and document analysis at SMP IT Cahaya Bangsa Mijen Semarang. The collected data was analyzed using the Miles and Huberman approach, involving the stages of data reduction, data presentation, and conclusions. The results showed that strengthening independent character and responsibility is implemented through humanistic concepts, especially in building motivation and awareness of the importance of setting priorities in academic activities. The humanistic concept is reflected in the integration of PAI subjects version of the Ministry of Religion and CS IT with humanist character, presentation of Islamic Education material that supports an attitude of responsibility, and an assessment system that encourages honesty based on active and fun learning. The aspect of self-education is more strongly implemented through extracurricular activities based on religious values, such as memorization of the Quran, archery, swimming, scouts, and taekwondo. These five extracurriculars are considered important to increase perseverance, self-confidence, leadership, self-discipline, and mental strength as elements of independence. The school also involves parents in guided discussion activities, including home visits, communication through WhatsApp groups, and specific meetings at school, to ensure the effective implementation of independent character and responsibility for students. This research contributes to providing in-depth insights into character strengthening practices in Islamic-based secondary schools, providing a foundation for the development of further strategies in improving the quality of character education. Penelitian ini bertujuan untuk menganalisis strategi penguatan karakter mandiri dan tanggung jawab di sekolah menengah berbasis Islam, dengan fokus pada implementasi konsep humanistik dalam pembelajaran. Metode penelitian yang digunakan adalah kualitatif, dengan pengumpulan data melalui observasi, wawancara mendalam, dan analisis dokumen di SMP IT Cahaya Bangsa Mijen Semarang. Data yang terkumpul dianalisis menggunakan pendekatan Miles dan Huberman, melibatkan tahap reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penguatan karakter mandiri dan tanggung jawab diimplementasikan melalui konsep humanistik, khususnya dalam membangun motivasi dan kesadaran akan pentingnya mengatur prioritas dalam kegiatan akademik. Konsep humanistik tercermin dalam integrasi mata pelajaran PAI versi Kemenag dan CS IT yang berkarakter humanis, penyajian materi Pendidikan Islam yang mendukung sikap tanggung jawab, serta sistem penilaian yang mendorong kejujuran berbasis pembelajaran aktif dan menyenangkan. Aspek pendidikan mandiri lebih kuat terimplementasikan melalui kegiatan ekstrakurikuler berbasis nilai-nilai keagamaan, seperti hafalan Al-Quran, panahan, renang, pramuka, dan taekwondo. Kelima ekstrakurikuler ini dianggap penting untuk meningkatkan ketekunan, rasa percaya diri, kepemimpinan, disiplin diri, dan kekuatan mental sebagai unsur kemandirian. Sekolah juga melibatkan orang tua dalam kegiatan diskusi terbimbing, termasuk kunjungan ke rumah, komunikasi melalui grup WhatsApp, dan pertemuan tertentu di sekolah, untuk memastikan efektivitas implementasi karakter mandiri dan tanggung jawab bagi siswa. Penelitian ini berkontribusi dalam memberikan wawasan mendalam tentang praktik-praktik penguatan karakter di sekolah menengah berbasis Islam, memberikan landasan bagi pengembangan strategi lebih lanjut dalam meningkatkan kualitas pendidikan karakter.